Diets, fruit and vegetable intake and nutritional status among children, adolescents and adults in the Philippines: A scoping review - Smith, Taryn J.; Angeles-Agdeppa, Imelda; Goyena, Eva; Gelli, Aulo; Olney, Deanna K. (Wiley, 2026)
Suboptimal diets contribute to the risk of malnutrition and non-communicable diseases across the life course. Globally, intakes of fruit and vegetables (F&V) fall below recommendations, including in the Philippines. To promote F&V intakes, understanding the extent of inadequate intakes across population groups and key drivers of dietary patterns is needed. This narrative scoping review was conducted to map the diet, F&V intakes and nutritional status in the Philippines. PubMed was searched using keywords specific to diet, F&V intake, and nutritional status, with 50, 24 and 22 articles meeting the inclusion criteria for diet, F&V intake, and nutritional status, respectively. Available evidence indicates that across all population and sociodemographic groups, diets lacked diversity, with high intakes of energy-dense, nutrient-poor foods, such as refined rice and sugar-based foods and beverages, contributing to inadequate micronutrient intakes. Intakes of F&V were especially low across all population groups. Stunting/short height, wasting and underweight were prevalent among children and adolescents, and micronutrient deficiencies (iron, zinc, vitamin A) were common among children < 5 years of age. More than one-quarter of adults were overweight or obese and demonstrated poor cardiometabolic health. A lack of published evidence identified through this search reported on pregnant and lactating women and women of reproductive age. Published evaluations assessing the impact of interventions or programmes to improve diets or F&V intake were limited. Additional research to fill these gaps will help design interventions and target entry points to improve diet diversity and F&V intakes across all population groups.